Integrated Photonics and Optoelectronics (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The target of this Reprint is to collect the latest research output in the field of integrated photonics and optoelectronics, including simulation theory, experimental work, and the latest corresponding applications, to demonstrate developing trends in integrated photonic and optoelectronic technologies. Thus, in this Reprint, various technologies, such as the properties of advanced materials, the nanofabrication process, functional nanostructures, and applications for sensors, as well as modulators related to integrated devices, will be featured. This Reprint is suitable for researchers aiming to broaden their mindset and creative more competitive, highly integrated devices to pave the way for the development of modern micro- and nanotechnology.